Nos bastidores da fé: compreendendo a manifestação da religião no casamento evangélico - Vilani, Cíntia Gemmo (2010)
Researchers have studied about the interface of religion in weddings, identifying that religious affiliation may be an important factor in the marital relationship. The purpose of this dissertation was to raise the elements that would promote discuss issues of marital satisfaction and conflict among married people and evangelical in order to obtain material for guidance and development of quality programs for married life. For this we used questionnaires to obtain information on participants, such as demographics (age, gender, financial and others), past behaviors and predicting future behavior, according to the personal beliefs of each participant, using also theMarital Adjustment Scale of Spanier (DSS - Dyadic Satisfaction Scale, 1976). The sample comprised 35 participants, 16 men and 19 women, mean age 36.80 years, with average deviation of 10.253, while 9 were followers of the neo- Pentecostal, 10 and 16 traditional church of the Pentecostal church, being subdivided into groups in relation to marital satisfaction. We work with the theme of marital satisfaction as the key as the present work, corroborated with the most points already stated in previous research, with emphasis on gender relations as a variable differential marital, surprising the greater number of women satisfied with respect tomen, the influence of religion can be seen in relation to paternal identification models, acting as a support network and training for moral and ethical values. The kinds of conflict and ways of facing the evangelical sample is similar to that of couples, regardless of religious variable